Indonesia’s Constitutional Court Decisions on Outsourcing Scheme: Balancing Protection and Efficiency? - Palguna, I Dewa Gede; Nurjanah, Ita; Padmawati, Ni Komang Tari; Dananjaya, I Komang; Halmadiningrat, I Made (Universitas Negeri Semarang, 2023)
This article explores the Indonesian Constitutional Court’s views through its decisions in shaping the practice of outsourcing in Indonesia based on the 1945 Constitution. The study was first conducted by analyzing Decision No. 012/PUU-I/2003 and later Decision No. 27/PUU-IX/2011. The novelty of this research is evident from the involvement of perspective in analyzing the outsourcing scheme in Indonesia as newly regulated in several laws, namely Job Creation Law and the Government Regulation in lieu of Job Creation Law. Using the normative legal research method, the authors used statutory, case, and conceptual approaches. Based on the research conducted, the authors found that the Constitutional Court aims to uphold the balance of companies’ efficiency and outsourced workers’ rights protection. The findings are evidenced by the Constitutional Court’s stance in a decision that implies that outsourcing is constitutional to enhance the State’s economy while simultaneously protecting the outsourced workers’ rights to ensure the fulfillment of their constitutional rights by setting two-fold models of protection. Therefore, even if new outsourcing scheme regulations are issued, the criterion of legality in future judicial reviews must involve determining whether such balance has been sufficiently met.